The Absurdalities of Mental Illness – A Narrative Inquiry into Psychiatric Diagnosis - Loodin, Henrik (Qualitative Sociology Review, 2009)
This text examines three life stories about becoming mentally ill and Albert Camus’ fictive narrative “The Stranger”. The main concern is how the social and psychiatry intervenes in the narrative that the interviewees give. Drawing from a reasoning in Michel Foucaults monograph Madness and Civilization and Dorothy Smiths work on relations of ruling the argument in this article is that when becoming mentally ill one is involved in a process of loosing agency in ones own life story. Illustratively with Camus novel the analysis unravel that the interviewees become strangers in their own life story.